2016
DOI: 10.1038/pr.2016.122
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal volume reduction is associated with intellectual functions in adolescents with congenital heart disease

Abstract: In adolescent survivors of cardiopulmonary bypass surgery for CHD, specific brain regions such as the hippocampus may show long-term persistent alteration and correlate with intellectual deficits, particularly with verbal and memory functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
66
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(72 citation statements)
references
References 44 publications
5
66
1
Order By: Relevance
“…Regional analysis revealed smaller volumes in the groups with CHD for cerebral white matter, cortical grey matter, cerebellum, thalamus, basal ganglia, hippocampus, and corpus callosum . However, only the difference in corpus callosum volume remained significant after controlling for total brain volume . Finally, Watson et al .…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Regional analysis revealed smaller volumes in the groups with CHD for cerebral white matter, cortical grey matter, cerebellum, thalamus, basal ganglia, hippocampus, and corpus callosum . However, only the difference in corpus callosum volume remained significant after controlling for total brain volume . Finally, Watson et al .…”
Section: Resultsmentioning
confidence: 91%
“…This review also summarizes the associations between brain structures and functional outcomes uncovered to date in young people with CHD. Overall, structural abnormalities measured both by conventional and by quantitative MRI were associated with poorer outcomes . More specifically, the presence of structural brain abnormalities identified by conventional MRI were associated with poorer performance on tests of intelligence, executive function, attention/hyperactivity, social cognition, motor performance, visuospatial/visuomotor skills, and academic achievement .…”
Section: Discussionmentioning
confidence: 93%
“…There was some overlap in the distributions of cortical difference between the d-TGA and SV groups confined to the parietal lobe. While previous study of a heterogeneous group of CHD patients has revealed reduction in total GM volume, cortical surface area, cerebellum, basal ganglia, hippocampus, and thalamus, parcellation of specific cortical gyri and evaluation of cortical thickness was not performed (25,26). Studies of children, adolescents, and young adults with CHD and 22q11.2 deletion syndrome revealed volume reductions in parietal, temporal, and occipital regions, as well as hippocampus (27,28).…”
Section: Articles Watson Et Almentioning
confidence: 96%
“…The incidence of WM injury reported is highly variable depending on the age at the time of surgery and the type of CHD. A recent study demonstrated reduced hippocampal volumes in adolescents who had undergone CPB surgery 58 ; the hippocampus is an important structure for learning and memory. Although several studies have addressed the effects of heart surgery on brain injury, the developmental abnormalities before surgery have received more attention recently.…”
Section: Neuroimaging In Chdmentioning
confidence: 98%